Physiology, biomechanics and injuries in table tennis: A systematic review - Ferrandez, C.; Marsan, T.; Poulet, Y.; Rouch, P.; Thoreux, P.; Sauret, C. (Science & Sports, 2020)
Objectives: Table tennis is a widely practiced sport, often described as a reaction sport. Therefore, players need to practice extensively that may expose them to overuse injuries. For optimizing training with limitation of the injury risk, the knowledges of table tennis physiology, biomechanics and epidemiology are of primary interest. Methods: For that purpose, a literature review has been made through a systematic search on three scientific databases. Overall, table tennis physiology is complex due to intense and intermittent efforts. It results that some technological challenges still need to be addressed to accurately quantify this physiology. Besides, current rules changes may modify the table tennis physiological requirements. Results: Findings in neurophysiology tend to define table tennis as an anticipation sport rather than a reaction sport and higher occulo-motor skills were found in table tennis population with respect to average population. Regarding biomechanics, some rare studies have been done but none had investigated the energy flow between the upper- and the lower-body, which would be interesting to understand how the energy generated by the footwork contributes to racket velocity. Conclusion: Finally, epidemiological studies lack of details on injury locations and diagnosis. These data could be of high interest to improve medical and training care.